Peran Kepemimpinan Transformasional dan Knowledge Sharing dalam Menstimulasi Perilaku Inovatif di Institusi Pendidikan - Hidayat, Agi Syarif; Rofaida, Rofi (Jurnal Ilmu Manajemen, 2021)
Human resources are the main production factors in implementing organizational innovation, so organizations need to encourage employees to have innovative behavior at work. Innovative behavior is not something that is genetically inherited, but something that can be learned and applied to employees in the organization. This research explores the influence of transformational leadership and knowledge sharing on innovative behavior. The research method used is a quantitative method. The population in this study were lecturers at 3 universities in the city of Cirebon. The number of samples in this study were 86 respondents. Data collection using a questionnaire instrument. Analysis of research data using multiple regression. The results showed that transformational leadership and knowledge sharing have a positive and significant influence on innovative behavior. In this study the knowledge sharing variable has a more dominant contribution compared to the transformational leadership variable to manage employee innovative behavior.